Pedagogical Aspects of Physical Training in Training of Specialists - Xazratkulov Askar Karimovich; Karimov Bekzod Boyqobilovich (Peerian Journals Publishing, 2022)
The most important function of physical training in the life of society which directed to the strengthen the body of the person and his moral. Physical training should be connected with the moral goals and noble aims. As far as the role of physical training consists of harmony development of the body of the human, it has tight connection with moral, labor, emotional and ethnics of the person
Keywords: physical training; society; health; development